An exploration of the shifts in imagined academic and civic identities across four history curriculum documents (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article analyses four curriculum documents in terms of the kinds of academic and civic identities that they would seek to produce. The curriculum documents are two South African (Curriculum 2005 [1997] and the Curriculum and Policy Statement [2011]) and two English (the first History National Curriculum [1991] and the most recent Secondary History National Curriculum [2014]). The theoretical underpinnings of the discussion of identity are Bernstein’s concepts of instructional and regulative discourse. The shifts in overall purpose and identity within the two contexts are striking. The first English national curriculum saw a tension between a focus on developing history learners who had a strong sense of national identity and using constructivist models that teach the learners the knowledge base of the subject. By contrast, Curriculum 2005 focused on attempting to create learners who were actively engaged with the problems of their current-day situation. By the second English national curriculum, a focus on making connections to current-day challenges had been introduced in addition to the existing concerns about national identity and understanding the way in which historians work. The Curriculum and Policy Statement (CAPS) reform in South Africa expressed greater concerns for developing historical thinking, but nevertheless retained a focus on actively engaged citizenship. The findings of this research provide a lens through which to consider current history curriculum reform and in particular, the ways in which curriculum documents imagine the learners that they would want to produce as both historians and citizens.
Keywords: Identity; Curriculum; Bernstein; Ministerial Task Team